Penalaran Statistik pada Peserta Didik Kelas IX - Fina Putri Damayanti; Widahyanti Widahyanti; Surya Sari Faradiba (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
This study aims to explore the ability to reason students in statistical material. This is motivated by the ability to reason statistics class IX students have not yet reached the highest level at the level of reasoning ability. This research is a qualitative research. The instrument used consisted of statistical question sheets and interview guidelines compiled based on indicators of statistical reasoning ability. The results of the study indicate that students are still unsure of the answers to the problems because basically students still have a level of informal quantitative reasoning ability.